Sportorthopädie | Sports Orthopedics - Hecksteden A; Meyer T (Deutsche Zeitschrift für Sportmedizin, 2018)
Optimizing precision and efficacy of measures on the individual level beyond what is achievable based on group means is the characterizing aim of personalized medicine. Sports medicine is a promising field of application for this concept and some aspects of individualization are already integral part of standard care e.g. relative exercise intensities based on reference values measured in the respective individual. To provide the evidence base for further advancement, the gap between medical practice focused on the individual and experimental research focused on the (true/mean) effect of an independent variable has to be bridged. To this end, methodological specifics of analyses on the individual level need to be taken into account. The resulting toolbox contains two main aspects: intraindividual repetition of measurements including the systematic combination of group-based and individual information and the joint consideration of multiple explanatory variables. These two features individualization and the consideration of multiple, possibly interacting determinants set personalized sports medicine apart from standard care. While these fundamental considerations are deducibly based on statistical principles, their full implementation is beset with many practical difficulties. Therefore, from the applied perspective, the ways of implementing personalized sports medicine will differ considerably depending on the specific task and the framework conditions in the field of application (e.g. preventive or elite sports). KEY WORDS: Individualization, Precision Medicine, Study Design, Variance Components, Variability